Biotypes of strains of Salmonella typhimurium of phage types 49, 204 and 193 - BARKER, RUTH M; OLD, D. C (Journal of medical microbiology, 1980)
Bacteriology Department, University of Dundee Medical School, Ninewells Hospital, Dundee DD1 9SY, Scotland Received September 3, 1979 Accepted September 20, 1979 Bio typing provided evidence of the phylogenetic relationships between strains of Salmonella typhimurium of phage types 49 and 204 and certain strains of phage type 193, which were interconvertible in phage types. All of 564 strains of phage types 49 and 204, 35 of which were chloramphenicol-resistant, were of biotype 26, whereas those of phage type 193 (91 strains) belonged to six different primary biotypes. Lines of descent are suggested for strains of phage type/biotype: 193/26a, 193/17gand 193/9f.